The Impact of Adolescent Sexual Harassment Experiences in Predicting Sexual Risk-Taking in Young Women. Issue 15 (August 2021) - Norcott, Candice; Keenan, Kate; Wroblewski, Kristen; Hipwell, Alison; Stepp, Stephanie
Early sexual behavior plays a vital role in female reproductive health. Victimization experiences such as sexual harassment may have a unique impact on girls' sexual health. We examined the prospective associations between sexual harassment during adolescence and high-risk sexual activity in early adulthood. Using mixed-effects logistic regression models, we tested associations between sexual harassment at ages 13 to 15 years and sexual risk behaviors at ages 16 to 20 years, controlling for depression and peer victimization. We used a community sample in Pittsburgh, PA. Through the Pittsburgh Girls Study, 2, 450 girls were recruited when they were between the ages of 5 and 8 years, with approximately equal numbers in each of the four age groups. Approximately half of the girls sampled were African American (52%), and 41% were European American. The remaining girls were described as multiracial or representing another race. Data were collected via an annual nonclinician administered interview. Results indicated that participants who experienced sexual harassment as adolescents (21%) were more likely to have multiple sexual partners and more likely to have contracted a sexually transmitted infection (STI) in early adulthood. Sexually active 16-year-olds who had been sexually harassed were over 3 times more likely to have had two or more partners in the past 30 days. These effects were maintained controlling for other types of peer victimization and depression. Sexual harassment was not significantly associated with birth control use. These results suggest that sexual harassment has downstream effects on women's health.